Effect of combination therapy of arthrocentesis and occlusal splint on nonreducing temporomandibular joint disk displacement - Peter Tvrdy; Petr Heinz; Jana Zapletalova; Richard Pink; Petr Michl (Biomedical Papers, 2015)
Objective: Arthrocentesis of the temporomandibular joint is a minimally invasive method of treatment located at the boundary between conservative and surgical therapy. It is usually performed on an out-patient basis under local anaesthesia. These days, arthrocentesis of the temporomandibular joint is used not only in cases of acute closed lock but also in the treatment of various temporomandibular disorders. The most frequent indication is acute anterior displacement of the articular disc without reduction. Treatment using occlusal splint is one of the most frequently used methods of conservative treatment. It is used mainly in the case of discopathies and myofascial pain. Aim: The aim of the study was to confirm that simultaneous use of the occlusal splint and arthrocentesis makes the treatment more effective in the case of detected disc dislocation without reduction. Materials, Methods and Results. From 2008 to 2013, 144 patients underwent arthrocentesis simultaneously using occlusal splint in the treatment of chronic closed lock. The study group consisted of a 130 (90.3%) women and 14 (9.7%) men. After 3 months of therapy, a good treatment outcome was found in 98 (68.1%) patients, 12 (85.7%) men and 86 (66.2%) women. The treatment did not have any effect in 46 (31.9%) patients, 2 (14.3%) men and 44 (33.8%) women. Conclusion: The simultaneous use of the occlusal splint and arthrocentesis makes the treatment more effective in the case of detected joint disc dislocation without reduction.